Elucidation of high removal efficiency of dichlorophen wastewater in anaerobic treatment system with iron/carbon mediator. (1st January 2022) - Li, Junjie; Li, Chunxing; Li, Yanlin; Wang, Ruming; Zhou, Mingdian; Zhao, Lixin; Pan, Xiaofang; Cai, Guanjing; Lv, Nan; Ning, Jing; Angelidaki, Irini; Zhu, Gefu
Abstract: Conductive material assisted anaerobic digestion presented much interest and promising prospect in pollutant removal during wastewater treatment. The present study deeply investigated the effect iron/carbon in anaerobic digestion for dichlorophen (DCP) degradation and methane production in synthetic DCP wastewater treatment. Results showed that nano-zero valent iron/activated carbon (nZVI/AC) and zero valent iron/activated carbon (ZVI/AC) gave higher chemical oxygen demand (COD) conversion (42.18% and 42.61%) and DCP removal (98.49 wt% and 99.00 wt%) in acidification step with better methane production from anaerobic digestion of the pretreated effluent. Same phenomenon occurred in the direct anaerobic degradation process due to the formation of galvanic cells between iron and carbon. In comparison, applying iron/carbon in acidification as pretreatment strategy plus following effluent anaerobic degradation showed higher efficiency in methane production and DCP removal than that of direct anaerobic degradation. Specifically, the methane production was 253.70 mL and 253.41 mL in subsequent anaerobic digestion system after nZVI/AC and ZVI/AC acidification pre-treatment, which was higher than 224.37 mL and 246.31 mL in direct anaerobic digestion system. Microbial community analysis showed that Clostridium_sensu_stricto_1 was the dominated bacteria due to its important role in DCP wastewater treatment. Both acetoclastic and hydrogenotrophic methanogens were enhanced in iron/carbon added systems, which was also agreement with the strengthen in related genes involved in methanogenesis. In conclusion, the present work systematically investigated the enhancement role of iron/carbon system in anaerobic digestion for DCP wastewater treatment and paved way for future application. Graphical abstract: Image 1 Highlights: Iron/carbon system was used for assisting anaerobic digestion of DCP wastewater. Iron/carbon system showed better performance in DCP removal and methane yield. Clostridium_sensu_stricto_1 was dominant bacteria with higher tolerance to DCP. Iron/carbon addition promoted the hydrogenotrophic methanogenesis pathway. The relative functional genes were promoted for better DCP wastewater treatment.